Synthesis and Antibacterial Activity of Some Coumarin Compounds - Desai, Pratibha; Champaner, A.C.; Desai, K.R. (Asian Journal of Chemistry, 2010)
Hydroxy coumarins are widely used as therapeutic agents. Several coumarin derivatives are constituents of plants so that plants are used for the treatment of disease in Ayurveda. They have been condensed with the S-triazines and the antibacterial activity of the modified coumarins has been tested against two bacterial species. All the derivatives are found moderately effective except 2-(4'methyl- 8'-acetyl coumarinyl-7' -oxy)-4-( 4' -methoxy anilino)-6-(2'methyl phenyl thioureido)-S-triazine, which shows highest antibacterial activity.